Simulation of Voltage Applied Effect on Carbon-Doped Boron Nitride Nanoribbon Hydrogen Gas Sensing Performance - Taib, Ainun Khairiyah; Johari, Zaharah; Abd. Rahman, Shaharin Fadzli; Mohd Yusoff , Mohd Fairus (ELEKTRIKA- Journal of Electrical Engineering, 2024)
Advanced materials have been widely investigated for numbers of electronics application. The aim is to provide higher device performance and mitigating the short channel effect. In this work, the performance of hydrogen sensing on carbon-doped boron nitride nanoribbon (BC2NNR) is investigated in response to different gate voltage applied, Vgs. The simulation is done to see the variation in the density of state (DOS) and the variation in the I – V characteristic. From the simulation, a significant effect is found when the Hydrogen gas was attached to different atom positions within the BC2NNR surface. A notable difference in sensitivity was achieved when Vgs is varied from 0 V to 2 V. In fact, a sensitivity of 85.07 % was achieved when the hydrogen molecule was attached to carbon atom. The result presented here may become guideline for experimentalists fabricating BC2NNR for gas sensing application.